LCA as a tool for road authorities in decision making process - Nurzyński, Karol; Panek, Aleksander (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
This work presents an introduction to LCA as a method for analysis of design variants for better decision-making process in infrastructural projects. Law and formal issues were analysed as a start point for this work. Current Polish law acts were compiled together with the aims pointed out by the European Commission in terms of Sustainable Public Procurement Policy. Authors presented state-of-the-art in LCA certification systems for road infrastructure projects including Greenroads rating system and currently being developed within the funds of the 7. Framework Programme ECOLABEL project.